Community Organizing in/as Adult Education - Thomas Archibald (Adult Education Research Conference, 2018)
The purpose of this paper is to explore the conceptual and practical overlaps of adult education and community organizing, in an effort to promote participation, equity, and justice through adult education.
Keywords: community organizing